Like it or not! Brand communication on social networking sites triggers consumer‐based brand equity. (16th December 2021) - Arya, Vikas; Paul, Justin; Sethi, Deepa
Abstract: This study examines how brand communication influences consumer‐based brand equity (BEQ) through social networking sites in the presence of brand attachment (BAT) as a mediator. The outcomes related to consumer‐BEQ, such as consumers' pay intention and loyalty to a brand and a brand's vocal ability, are also explored in this study. An empirical investigation for 498 responses was carried using Smart‐PLS, Process‐macro & artificial neural network modeling based hybrid approach. The analysis indicates that brand consumer‐BEQ is high when a brand's communication on social media platforms is positive. A strong mediating role of BAT is confirmed. The study is unique in terms of explaining the role of brand communication on social networking sites and its impact on consumer‐BEQ in the presence of BAT as a mediator. While focusing on Millennials' tech‐savvy characteristics and considering SNSs as an advanced tool for brand communication, brands should refine their marketing strategy.